Active repair of a dinuclear photocatalyst for visible-light-driven hydrogen production - Pfeffer, Michael G.; Müller, Carolin; Kastl, Evelyn T. E.; Mengele, Alexander K.; Bagemihl, Benedikt; Fauth, Sven S.; Habermehl, Johannes; Petermann, Lydia; Waechtler, Maria; Schulz, Martin; Chartrand, Daniel; Laverdiere, Francois; et al. (Nature Chemistry, 2022)
The molecular apparatus behind biological photosynthesis retains its long-term functionality through enzymatic repair. However, bioinspired molecular devices designed for artificial photosynthesis, consisting of a photocentre, a bridging ligand and a catalytic centre, can become unstable and break down when their individual modules are structurally compromised, halting their overall functionality and operation. Here we report the active repair of such an artificial photosynthetic molecular device, leading to complete recovery of catalytic activity. We have identified the hydrogenation of the bridging ligand, which inhibits the light-driven electron transfer between the photocentre and catalytic centre, as the deactivation mechanism. As a means of repair, we used the light-driven generation of singlet oxygen, catalysed by the photocentre, to enable the oxidative dehydrogenation of the bridging unit, which leads to the restoration of photocatalytic hydrogen formation. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-04-20